Peningkatan Manajemen Keuangan Umkm Melalui Pelatihan Dan Pendampingan Penghitungan Harga Pokok Produksi - Yuliana, Lutfiah; Budiantara, Martinus (LPPI UMN AL WASHLIYAH, 2024)
The challenges faced by MSMEs, especially those related to financial management, often become obstacles in the quest to thrive and compete in an increasingly complex market. In managing a business, it is important to understand the concept of cost of production preparation thoroughly. Cost of goods sold becomes the basis for setting the right selling price and ensuring business sustainability and profitability. This community service activity aims to provide guidance and training on calculating production costs to determine selling prices to MSMEs, namely Wisanggeni Restaurant MSMEs and Cak-Cik Fried Rice MSMEs in Yogyakarta, Bantul Regency, Sedayu District. This activity will be carried out on February 17-19, 2024. The stages of this training activity are: 1) Survey 2) Material delivery stage 3) Training and guidance 4) Results and evaluation. The results of this community service activity are an increase in understanding related to COGS from 30% to 80%, then after training and mentoring it increases to 100%, so it can be concluded that training and mentoring are effective in achieving the desired goals, namely increasing the understanding and skills of MSME actors in calculating and compiling cost of goods produced to set selling prices. Keywords: Cost of Goods Manufactured, Financial Management, MSME.